(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
A 20 years old male presented with Class-I malocclusion with crowding and lock bite on upper right and left lateral incisors. Treatment involved extraction of all first premolars. The alignment of teeth in both arches were achieved by edgewise orthodontic therapy. Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1